Analisis Strategi Bersaing Berbasis Bisnis Syariah pada Rumah Makan Minang Maimbau di Nagari Aia Gadang Kecamatan Pasaman Kabupaten Pasaman Barat - Amelia Amelia; Novera Martilova (Jurnal Riset Ekonomi dan Akuntansi, 2024)
The aim of this research is to find out what the Sharia Business Based Competitive Strategy is at the Minang Maimbau Restaurant in Nagari Aia Gadang, Pasaman District, West Pasaman Regency and to find out the obstacles and solutions faced by the Minang Maimbau Restaurant in Implementing the Competitive Strategy. This research uses qualitative research methods, while the data analysis method used is SWOT analysis, where information is collected through documentation. The Minang Maimbau restaurant is a case study for this research. The owner of the Minang Maimbau restaurant and consumers and employees are the sources of information for this research. From the results of the SWOT matrix research, it is known that Minang Maimbau restaurants must maximize service improvement by utilizing technology and maintaining quality taste at affordable prices in order to retain existing consumers. The competitive strategy carried out by Minang Maimbau Restaurant is improving facilities and infrastructure, adding product innovation, establishing cooperative relationships with Gofood services. The obstacle faced by Minang Maimbau Restaurant in implementing a competitive strategy is the frequent turnover of employees which results in instability in service and the difficulty of maintaining customer loyalty.